The Pedagogical Role of Verification in Supporting Mathematical Justification within the ACTIVER Learning Model - Sri Lestari; Kartono Kartono; Masrukan Masrukan; Emi Pujiastuti (MASI Mandiri Edukasi, 2026)
Mathematical justification requires students to examine and defend mathematical claims rather than merely produce correct answers. However, vocational students often experience difficulty constructing defensible mathematical arguments, while verification may be limited to checking final answers. This study examines the pedagogical role of Verify Understanding within ACTIVER, a differentiated mathematical reasoning learning model developed using the ADDIE framework. The broader study was conducted from March 2025 to May 2026. The comparative implementation involved 216 Grade X vocational high school students across six intact classes and was delivered over eight meetings. Quantitative evidence included posttest achievement, mastery proportions, and normalized gain, while implementation evidence was examined in relation to predefined justification indicators. In the limited trial, the ACTIVER group achieved a higher posttest mean than the comparison group (83.86 vs. 64.39), t(70) = 17.232, p < .001, d = 4.06. In the broader trials, experimental means of 84.44 and 85.39 exceeded comparison means of 69.56 and 71.00, respectively (p < .001). Mastery proportions and learning gains consistently favored ACTIVER. Verification provided structured opportunities to examine evidence, respond to critique, and revise mathematical reasoning. Its contribution should nevertheless be interpreted within the integrated ACTIVER sequence rather than as an independently tested intervention.